Qualidade do gasto público destinado à educação básica nos municípios do COREDE do Médio Alto Uruguai - Silva, Fábio da (2024)
Governments faced with continuous resource constraints and public spending limitations have redefined their roles, prioritizing governmental policies for areas such as education. However, financial resources directed towards education do not necessarily translate into an improvement in the quality of public services provided. Therefore, the objective was formulated to analyze the level of efficiency of public spending directed towards basic education in elementary schools in the municipalities of the COREDE Médio Alto Uruguai, from 2008 to 2021, employing Data Envelopment Analysis (DEA) for both initial and final grade series. The results for initial and final grade series regarding the maximum number of Decision Making Units (DMUs) considered benchmarks, within the specified time frames, were 66.66%, corresponding to 14 municipalities. Regarding the number of times municipalities reached the maximum relative efficiency index, the result for initial grade series was 59.18%, while for final grade series it was 57.82%. The results indicate that public resources did not reach their maximum potential utilization for many municipalities, demonstrating misappropriation of public funds. Furthermore, the best (efficient) results do not clearly correlate with higher utilization of public resources, as municipalities with higher expenditures do not rank higher in efficiency. Therefore, several considerations can be drawn: there is no homogeneity or technical pattern that allows identifying similarities among the best or worst ranked; it is not possible to affirm a relationship between municipality size and efficiency; no association was found between the amount spent per student or per resident and the efficiency index; and, high spending on education is not a sufficient condition for achieving better academic performance. Thus, current resource investment policies that adopt the existing educational structure have not been sufficient to bring about necessary improvements, necessitating more attention to resource utilization rather than the amount invested.